Atomic simulation of wrinkling and deformation in curved graphene nanoribbons under boundary confinement. (5th January 2016) - Fan, Yu-Cheng; Fang, Te-Hua; Huang, Chao-Chun; Chen, Tao-Hsing
Abstract: Molecular dynamics simulation is used to investigate the properties of the curved and planar monolayer graphene nanoribbons (GNRs) under boundary confinement. The wrinkles are formed in curved-armchair GNRs not in curved-zigzag GNRs. With temperatures of 300–900 K and curvature radii of 3–6 nm, the wavelength of wrinkles did not change obviously. In nanoindentation tests, the zigzag graphene comparing to the armchair graphene had the larger contact stiffness about 50%. Further the concave graphene comparing to the convex graphene showed the higher contact stiffness due to its higher Young's modulus. Graphical abstract: Highlights: The wrinkling behavior is discussed at the curved-armchair graphene under boundary confinement. The zigzag graphene comparing to the armchair graphene has the larger contact stiffness about 50%. The wrinkles seriously reduce the contact stiffness of the graphene. Influence of temperature, curved radius, and indentation velocity on contact stiffness is studied.